Comparison of monensin sodium and xylanase in high fiber poultry diets - Snyder, Kendra R.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Antimicrobials, such as monensin sodium, have been used to increase nutrient digestibility in poultry diets. However, consumers have been putting increasing pressure on producers to limit the amount of antimicrobials used in feeds. Therefore, producers have been searching for replacements of antimicrobials. Another common additive is exogenous xylanase, an enzyme used to improve digestibility in high fiber feeds. Thus, the objective of this study was to compare the ability of monensin sodium and xylanase to improve digestibility in poultry diets of different fiber levels. This experiment was conducted with a total of 216 1-day old Cobb chicks, 6 chicks/cage. Treatments and birds were randomly assigned to battery cages. The dietary treatments included a corn-based control, wheat-based control, a corn- or wheat-based diet containing 0.10 g/kg monensin sodium (Coban 90), or a corn- or wheat-based diet containing 16,000 betaxylanse units/kg beta 1-4, endoxylanse enzyme (Econase XT). The treatments were fed over a 21-day period, while BW and feed intake were monitored weekly to determine overall weight gain, total feed intake, and FCR. The data was analyzed using GLIMMIX and SAS with the cage as the experimental unit and the treatments as the fixed effect. There was a treatment impact of P < 0.01 on final BW, feed intake, and FCR. The corn-based control diet improved FCR by P < 0.05 compared to the wheat-based control diet, but when compared to the corn-based monensin sodium and xylanase treatments, there was no statistical difference (P > 0.05) in the FCR. However, when comparing the controlled wheat-based diet to the wheat-based xylanase treatment, the FCR improved (P < 0.05). There was no statistical impact of monensin sodium due to the low disease pressure exhibited. However, this experiment suggests xylanase improves the nutrient digestibility in wheat-based diets to a level that compares to corn-based diets.
Keywords: Spring 2017